Reativação Ocular da Toxoplasmose Durante a Gravidez - Olival, V (2014)
Toxoplasma gondii infection reactivation is more likely to occur during pregnancy on account of the characteristic physiologic immunotolerance. Visual impairment and retinal scars in a previously infected individual allows the diagnosis. In an immunocompetent woman,transplacentary infection is unlikely to occur, but that possibility carries a well known great risk for the fetus. Fetal infection should be carefully excluded in the amniotic fluid and prophylaxis should be promptly instituted if fetal infection is not proven to have already happened. We report a case of a 30 year-old Brazilian woman diagnosed an ocular reactivation of toxoplasmosis with no evidence of fetal transmission during the initial workup. A careful ultrasound follow-up was performed during pregnancy and a espiramicin-based prophylactic regimen was initiated. After delivery, either the newborn serum analysis nor the hystopathological study of the placenta were suggestive of T. gondii infection.